Pengaruh Quick Ratio, Debt to Asset Ratio, terhadap Return on Asset pada PT. Unilever Indoonesia. Tbk yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2020 - Suharmiyati Suharmiyati; Yenny Iskandar; Albetris Albetris (Universitas Batanghari, 2022)
One of the successes of a company is seen from its profitability. With profitability, the company can assess its performance and for third parties it is used as a basis for making investment decisions. One way to test the company's profitability is to return on assets. Return On Assets can show how a company uses its assets to earn a profit. The purpose of this research is to find out whether Quick Ratio (QR) and Debt to Equity Ratio (DER) have an effect on Return On Assets (ROA) at PT. Unilever Indonesia Tbk Period 2011-2020. The method used in this study is a descriptive verification method that uses a quantitative approach. The types and sources of data used are secondary, originating from the financial statements of PT. Unilever Indonesia Tbk Period 2011-2020. The operational variables in this study are the Quick Ratio as X1, Debt to Equity Ratio as X2 and Return On Assets as Y. Simultaneously, F count 20,471> F table (9.55) then Ho is rejected and Ha is accepted. This means that the Quick ratio and debt to asset ratio variables together have a significant effect on return on assets at PT. Unilever Indonesia Tbk on the Indonesia Stock Exchange.